MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMK PELITA GEDONG TATAAN - Ayuningsih, Rih; Muhtarom, Muhtarom; Ngarifin, Syeh Al (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2018)
AbstractThis study aims to determine the implementation of Human Resource Management in SMK Pelita Gedong Tataan District Pesawaran. To know the successful implementation of Human Resource Management related to the development of teacher professionalism and discipline in order to improve the quality of education in SMK Pelita Gedong Tataan. This research is a qualitative field research with data collection techniques that are: observation, interview, and documentation. Data analysis in this research is descriptive analysis technique.In implementing Human Resource Management, steps taken by SMK Pelita Gedong Tataan begins with planning everything that will be done in improving the quality of education, such as with the recruitment and selection of educators and education, then planning is organized according to the needs of the school. The next step is the implementation of a predetermined plan and guidance then supervision and evaluation is the final step in implementing Human Resource Management related to teacher professional development and discipline in order to improve the quality of education.Implementation of Human Resource Management in an effort to improve the quality of education in SMK Pelita Gedong Tataan Gedong Tataan District Pesawaran Regency has been quite successful in improving the quality of education. This is indicated by the passing rate of students who reach one hundred percent.